Innovation in global entrepreneurship education : teaching entrepreneurship in practice - Neck, Heidi M.; Liu, Yipeng (Cheltenham, UK: Edward Elgar publishing, 2021)
"As entrepreneurship education grows across disciplines and permeates through various areas of university programs, this timely book offers an interdisciplinary, comparative and global perspective on best practices and new insights for the field. Through the theoretical lens of collaborative partnerships, it examines innovative practices of entrepreneurship education and advances understanding of the discipline. Exploring and showcasing how global collaboration can foster entrepreneurship education, international contributors share their experiences as educators, scholars and thought-leaders involved in the Babson Collaborative. Chapters illustrate the challenges faced by educators and creative methods for tackling them, offering useful insights from a range of disciplinary perspectives. Highlighting the significance of the field to higher education environments, this book encourages active participation in entrepreneurial practice and collaboration between stakeholders and disciplines to ensure high-quality education in a variety of settings. This insightful book is a rousing and inspiring view of entrepreneurship education for scholars and academic entrepreneurs who are working to build robust education ecosystems in the field"--
Part I. Building bridges across the university for entrepreneurship -- Part II. Teaching and learning entrepreneurship -- Part III. The impact of entrepreneurship education and new directions.
Includes bibliographical references and index.
Keywords: Entrepreneurship -- Study and teaching; Entrepreneuriat -- Étude et enseignement; Entrepreneurship -- Study and teaching